Bridging Research and Action: Assisting in the Preparation of Data-Based Poverty Alleviation Plans in Local Governments - Novayanti Sopia Rukmana S; Sulmiah Sulmiah; Sirajuddin Saleh; Anna Fiulaizi; Anisa Fitri (PT. Global Research Collaboration, 2025)
Poverty is a multidimensional challenge that requires strategic and evidence-based planning. This community engagement initiative aims to strengthen the capacity of a local government institution in developing a data-driven poverty reduction plan through a collaborative and systematic policy-oriented approach. The program involved identifying strategic issues across multiple welfare dimensions, including education, health, consumption, employment, basic infrastructure, and food security. Participatory methods such as focus group discussions, technical workshops, and data validation sessions were applied to produce a comprehensive poverty profile at both macro and micro levels. The findings indicate that the local government faces complex poverty conditions with vulnerable populations concentrated in several areas and persistent gaps in key welfare indicators. The resulting plan outlines targeted interventions, program priorities, resource allocation, and measurable performance indicators for the medium-term planning period. This initiative demonstrates how policy-oriented academic engagement can enhance institutional capacity to formulate more effective, evidence-driven, and accountable poverty reduction strategies